2004
DOI: 10.1021/ic049512v
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual 3D Coordination Polymer Based on Bridging Interactions of the Nucleobase Adenine

Abstract: The first 3D coordination polymer containing a nucleobase as a bridging ligand, [[Cu2(mu-ade)4(H2O)2][Cu(ox)(H2O)]2 x approximately 14H2O]n (1), has been synthesized by reaction of adenine (Hade) with a basic solution of K2[Cu(ox)2] x 2H2O (ox = oxalato dianion). Compound 1 crystallizes in the trigonal space group R3 with a = b = 31.350(1) angstroms, c = 14.285(1) angstroms, V = 12158.7(10) angstroms3, and Z = 9. X-ray analysis shows a covalent 3D network in which the copper(II) centers are bridged by tridenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 32 publications
(28 reference statements)
0
68
0
1
Order By: Relevance
“…To date, the most commonly reported bio-MOFs are based on Adenine (Ade). [52,[115][116][117][118][119][120] Despite the advantages, bio-MOFs containing nucleobases are not exhaustive, which may be the result of no control over their binding modes to metal ions, and their inherent lack of symmetry which inhibit packing in the formation of crystalline materials. Most of the examples reported in the literature highlight the rich coordination modes of Ade leading in the formation of highly porous bio-MOFs.…”
Section: Nucleobasesmentioning
confidence: 99%
“…To date, the most commonly reported bio-MOFs are based on Adenine (Ade). [52,[115][116][117][118][119][120] Despite the advantages, bio-MOFs containing nucleobases are not exhaustive, which may be the result of no control over their binding modes to metal ions, and their inherent lack of symmetry which inhibit packing in the formation of crystalline materials. Most of the examples reported in the literature highlight the rich coordination modes of Ade leading in the formation of highly porous bio-MOFs.…”
Section: Nucleobasesmentioning
confidence: 99%
“…17 Garcia-Teran et al reported a complex formed by adenine and Cu. 18 Rosi and co-workers synthesized a metal-organic framework using Zn(II) and adenine, where Zn was coordinated via oxygen and controlled drug release was demonstrated. 19 Kimizuka and co-workers prepared supramolecular networks of adenosine monophosphate (AMP) with various lanthanides, where both oxygen and nitrogen ligands are proposed to participate in metal binding.…”
mentioning
confidence: 99%
“…Adeninaz eratutako lehenengo MOFen artean [Cu 4 (μ 3 -adeninato-κN3:κN7:κN9) 4 (oxalato) 2 (H 2 O) 4 ] n koordinazio konposatua aipa dezakegu [10]. Konposatu horretan [Cu 2 (μ-adeninato) 4 …”
Section: Zubi Estekatzaile Moduan Diharduten Base Nitrogenatuek Eraikunclassified